Patient perceptions of multiple sclerosis and its treatment - de Seze J, Borgel F, Brudon F (Patient Preference and Adherence, 2012)
Jérôme de Seze1, Florent Borgel2, Frédérique Brudon31Department of Neurology CHRU de Strasbourg, Strasbourg, 2Medical Center, Grenoble, 3Clinique du Tonkin, Villeurbanne, FranceBackground: In order to improve the treatment outcome in multiple sclerosis, it is important to document the factors that influence adherence to therapy. The purpose of this study was to determine patient perceptions and awareness of multiple sclerosis and its treatment, treatment adherence, and impact on quality of life and daily living.Methods: This was a cross-sectional observational study performed in France. Each participating neurologist included the first three patients with relapsing-remitting multiple sclerosis who consulted after the start of the study. Data on clinical features were collected from a physician questionnaire and on disease and treatment perception and on quality of life from a patient autoquestionnaire.Results: A total of 175 neurologists entered 202 patients in the study. The mean duration of disease was 8.0 ± 7.0 years, and immunomodulatory treatment had been administered for a mean duration of 3.0 ± 2.0 years. A total of 166 patients (82.2%) were treated with interferon-ß preparations and 36 patients (17.8%) with glatiramer acetate. Eighty-five patients (42.1%) reported missing their injections from time to time and 36 patients (17.8%) reported “drug holidays”. The most frequently given reason for nonadherence was forgetfulness (38.7% of cases). Eighty-six patients (42.6%) and 70 patients (34.7%) claimed to be well informed about their disease and treatment, respectively. Adherence was significantly higher in well informed patients (P = 0.035). The majority of patients (176 patients, 87.1%) intended continuing their current treatment and 49.5% considered that their current treatment might reduce relapses. The most frequently reported side effect was muscle pain (124 patients, 61.4%).Conclusion: Patient understanding of treatment for disease enhances treatment adherence. Greater patient involvement in disease management requires better communication between physicians and their patients.Keywords: multiple sclerosis, patient adherence, quality of life